(3cja JfTiA eTQhYG UZjQG?s - (3hGjJ , (B. (3f (B. (3J (B.s; (3f (B. (3J (B. (3hGjJ(B.s ((3GdbGgQI (B:s (3OGQ GdaGQhb ddfTQ hGdJhRjY(B.,s, 2005)
(3jJfGhd GdcJGH GdeTGQjY GdUZjQI (B.s
(3GdeTGQjY GdUZjQI(B.s
Adult.
Keywords: (3GdeTGQjY GdUZjQI(B.s